The State of African Cities 2014 re-imagining sustainable urban transitions - UN HABITAT (Nairobi UN HABITAT, 2014)
The African continent is currently in the midst of simultaneously unfolding and highly significant demographic, economic, technological, environmental, urban and socio-political transitions. Africa?s economic performance is promising, with booming cities supporting growing middle classes and creating sizable consumer markets. But despite significant overall growth, not all of Africa performs well. The continent continues to suffer under very rapid urban growth accompanied by massive urban poverty and many other social problems. These seem to indicate that the development trajectories followed by African nations since post-independence may not be able to deliver on the aspirations of broad based human development and prosperity for all. This report, therefore, argues for a bold re-imagining of prevailing models in order to steer the ongoing transitions towards greater sustainability based on a thorough review of all available options. That is especially the case since the already daunting urban challenges in Africa are now being exacerbated by the new vulnerabilities and threats associated with climate and environmental change.
Keywords: Urbanisation